Incidental findings of borderline ovarian tumor or ovarian cancer – real-world data on surgical and oncological outcomes - Joder, Carmen; Smaadahl-Wey, Celine; Zumwald, Lara; Saner, Flurina; Rauh, Claudia; Hofer, Seline; Wampfler, Julian; Schlootz, Saskia; Rau, Tilman; Christe, Lucine; Solass, Wiebke; Imboden, Sara; et al. (Frontiers in Oncology, 2024)
IntroductionCentralization of ovarian cancer treatment is associated with higher rates of optimal surgery and longer survival. However, preoperative diagnosis of ovarian cancer is challenging and some diagnoses are made incidentally after surgery. This study investigated the surgical and oncological outcomes of patients with incidental findings of borderline ovarian tumors or ovarian cancer who were centralized postoperatively and treated with a two-stage surgical procedure, and compared these with those of patients with adnexal masses of suspected malignancy who were offered a single-stage surgical procedure with intraoperative frozen section in a tertiary hospital.MethodsA database of 390 patients with adnexal masses and surgical treatment at the Bern University Hospital, Switzerland was retrospectively reviewed to identify patients with borderline ovarian tumors or ovarian cancer between 2010 and 2020.ResultsAmong 390 patients with adnexal masses, 223 were diagnosed with a borderline ovarian tumor or ovarian cancer. Compared with patients with suspected malignancy and a centralized single-stage surgical procedure, patients with an incidental postoperative malignancy diagnosis and a two-stage surgical procedure underwent more surgical interventions (1.3 vs. 2.1 p<.001) and had a longer time interval from diagnosis to initiation of chemotherapy (33.3 vs. 45.1 p=.005) and to completion of surgical cytoreduction (31.9 vs. 73.7 days, p<.001). However, there were no differences in the rates of complete cytoreduction (90.0% vs. 93.2%, p=.719), intraoperative (11.3% vs. 13.7%, p=.664) or postoperative (38.7% vs. 37.0%, p=.884) complication rates, and number of hospitalization days (11.1 vs. 12.0 days, p=.369). An incidental diagnosis of malignancy with postoperative referral was neither associated with an increased risk of recurrence (hazard ratio (HR) 0.8, 95% confidence interval (CI) 0.6-1.8, p=.839) nor death (HR 0.7, 95% CI 0.4-1.1, p=.113), and there was no difference in mean recurrence-free survival between the study subgroups.DiscussionAlthough patients with incidental findings of borderline ovarian tumors or ovarian cancer treated with a two-stage surgical procedure had a longer time to completion of surgical staging and initiation of chemotherapy, our results showed no negative impact on oncological outcomes.